Pembatalan Perkawinan Karena Adanya Hubungan Saudara Sepersusuan dan Implikasi Hukumnya Terhadap Status Anak yang Dilahirkan: Studi Kasus Terhadap Putusan Pengadilan Agama Tembilahan No. 468/PDT.G/2023/PA.TBH - Rizka Nadhira; Endah Hartati (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Marriage, as defined by the Marriage Law, is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family founded upon the belief in the One Almighty God. However, if a marriage does not fulfill the requirements for a valid marriage, it may be annulled. One of the grounds for annulment is the existence of a milk kinship between the husband and wife, which, under Islamic law, holds the same legal implications as a blood relationship. This research aims to analyze the case of marriage annulment adjudicated by the Religious Court of Tembilahan under Decision No. 468/Pdt.G/2023/PA.Tbh, due to the presence of a milk kinship between the spouses. It examines the legal consequences of the annulment on the civil status of the husband and wife and the legal implications for the status of children born from the marriage. Milk kinship constitutes a legitimate ground for annulling a marriage, which results in changes to the legal status of the spouses and the position of the children. The annulment of a marriage on the grounds of milk kinship restores the civil status of the husband and wife to their original state as though the marriage had not taken place. However, children born from such a marriage are still considered legitimate and retain all the rights associated with legitimate children.